Localization and characterization of SMP-containing proteins in Membrane Contact Sites - Huércano Rubens, Carolina; Sánchez-Vera, Victoria; Percio-Vargas, Francisco; Morello-López, Jorge; Botella-Mesa, Miguel Ángel; Ruiz-López, Noemí (My University, 2021)
Membrane contact sites (MCS) are discrete regions where two membranes from different organelles are closely apposed (10-30 nm). In those regions, non-vesicular transfer of lipids takes place to ensure proper organelle functioning. Arabidopsis SYT1 is one of the best characterized MCS protein, and it plays a relevant role in tolerance to abiotic stresses. SYT1 is a SMP (synaptotagmin-like mitocondrial lipid binding domain) containing protein localized at ER-PM contact sites. Recent studies suggest that this protein transfer glycerolipids between these two membranes. However, little is known about other SMP-containing proteins in plants, as their localization or their role in abiotic stress. We have focused on studying the rest of SMP-containing proteins in Arabidopsis thaliana and Solanum lycopersicum. To identify them, human E-Syt1 sequence was used to find the remote orthologues in plants. An interesting highlight of those results was that some SMP-containing proteins are exclusive from plants, there are no orthologues in human nor yeast. The subsequent step was the study of their subcellular location, that was carried out in Nicotiana benthamiana by transient expression of the SMP-containing proteins from Arabidopsis and Solanum, followed by confocal microscopy imaging. We have found that those proteins locate in different MCS across the cell: SYT6, NTMC2T6 and Tex2 localise in ER-Golgi contact sites, NTMC2T5 in ER-Chloroplast contact sites, and we have also confirmed that Solanum CLB1 and SYT5 localized at ER-PM contact sites as their Arabidopsis counterparts. Additionally, we have analysed the root growth, seed germination rates and fully expanded cotyledons of Arabidopsis mutants for these genes in media supplemented with salt or ABA, and our results suggest that some of these proteins might be implicated in abiotic stress signalling through an ABA pathway.
Keywords: Proteína SMP; Lípidos; Biología vegetal - Congresos; SMP, Lipid, SYT